Pengaruh Konsumsi Kombinasi Jus Bayam Dan Jambu Biji Terhadap Kenaikan Kadar Hb Pada Mahasiswa - Kartikasari, Anggit; Indrayani, Indrayani (Jurnal Riset Hesti Medan, 2023)
Iron deficiency anemia is a decrease in the number of red blood cells caused by too little iron. Based on a preliminary study of 10 respondents, it was found that 60% of respondents had anemia and 40% did not have anemia. The study aims to determine the effect of a combination of spinach and guava juice on increasing in Hb levels. The research uses quantitative methods with the type of experimental Quasi research and the design used is Nonequivalent Time Sample Design or One Group Pretest-Posttest Design. The total population of Students is 69 people with purposive sampling technique obtained samples of 18 people. The analyses used are univariate and bivariate using Paired Sample T Test. The results of the seven-day study showed that the rate of anemia before juice was 22.2% and after juice is 5.6%. The average increase in Hb levels before Juice was 12.2 gr/dl and after Juice is 13,0 g/dl with a difference of 0.8 gr/ dl, using Paired Sample T Test obtained a p-value of 0.001 (p<0.05). The results of the study show that there was an effect of combined consumption of spinach and guava juice on increasing hemoglobin levels in Midwifey Students of Institute of Health Science Kuningan in 2019. Recommendations for health professionals, especially midwives, to provide services for anemia prevention through health promotion and for midwifey institutions are used for advanced research.